Prognostic value of myocardial I-123metaiodobenzylguanidine imaging in patients with atrialfibrillation; European Journal of Nuclear Medicine and Molecular Imaging; Vol. 42, suppl. 1 : European Association of Nuclear Medicine, EANM'15 - Saushkina Yu. V. Yuliya Vyacheslavovna; Lishmanov Yu. B. Yury Borisovich; Kisteneva I. V. Irina Valerjevna; Popov S. V. Sergey Valentinovich (2015, 2015)
Title screen